Comparison of the Effect of Three Irrigation Techniques and Root Canal Preparation Size on Sodium Hypochlorite Penetration into Root Canal Dentinal Tubules - Pakit Tungsawat; Pondpun Arunrukthavorn; Phawinee Phuntusuntorn; Suphakit Opatragoon; Pharsiri Sirirangsee; Surat Inklub (Hindawi Limited, 2021)
Objective. This study aims to compare the effects of conventional syringe irrigation (CSI), passive ultrasonic irrigation (PUI), and innovative sonic-powered irrigation (EDDY) on the penetration of sodium hypochlorite (NaOCl) solutions into root canal dentinal tubules at different levels of the root canal. Materials and Methods. One hundred ninety-two extracted first mandibular premolars of 17- to 25-year-old patients were decoronated 13 mm from the root apices and separated into two groups according to apical preparation sizes (APS) 25 and 40. The root canals were dried with a paper point and stained in crystal violet for 72 hours. Each APS group was separated into three groups according to irrigation techniques, as follows: CSI, PUI, and EDDY. Roots were perpendicularly resected to the long axis at three levels (coronal, middle, and apical). Photomicrographs were taken of all three cross-sections of each tooth under a stereomicroscope. The depth of the bleached zone was measured with ImageJ software. The data were analyzed by Welch's analysis of variance and an independent t-test (p = 0.05). Results No penetration was found at the apical level in the CSI25, CSI40, and PUI25 groups. The EDDY25 and EDDY40 groups showed the most significant penetration at the middle and apical levels compared to the other groups (p < 0.05). Conclusions. Within the limitations of this study, irrigation techniques and APS affect the penetration depth of NaOCl into the root canal dentinal tubules. In terms of irrigation techniques, the penetration was deepest when EDDY was used, followed by PUI and CSI. In terms of APS, NaOCl penetrated deeper into APS40 than APS25. The use of the EDDY irrigation technique in APS25 can improve the penetration of NaOCl into root canal dentinal tubules at the apical level.